(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
In this paper, the concept of n-upper level soft set is introduced together with some of its properties. It is shown that some properties holding in n-level soft set do not hold in n-upper level soft set. It is further demonstrated that both the first and the second decomposition theorems fails in n-upper level soft set